Evaluation of viscosity and thermal conductivity models for CO2 mixtures applied in CO2 cryogenic process in carbon capture and storage (CCS). (August 2017) - Tan, Yuting; Nookuea, Worrada; Li, Hailong; Thorin, Eva; Yan, Jinyue
Highlights: Viscosity and thermal conductivity models of CO2 mixtures were evaluated. Recommendations for viscosity and thermal conductivity model selection were given. The impact of thermal conductivity on heat exchanger design is noticeable. Viscosity and thermal conductivity models can be improved further. Abstract: The cryogenic process is used for CO2 purification in oxy-fuel combustion power plant, and multi-stream heat exchanger is one of the most important components. Viscosity and thermal conductivity are key transport properties in the design of plate-fin multi-stream heat exchanger. It is necessary to evaluate the impacts of viscosity and thermal conductivity models on the design of the heat exchanger. In this paper, different viscosity models and thermal conductivity models for CO2 mixtures with non-condensable impurities were first evaluated separately by comparing the calculated results with experimental data. Results show that for viscosity, the absolute average deviation of KRW model is the smallest, which is 1.3%. For thermal conductivity, model developed by Ely and Hanley, with absolute average deviation of 3.5%, is recommended. The impact of property models on the design of plate-fin multi-stream heat exchanger was also analyzed. The thermal conductivity model has a noticeable impact on the plate-fin multi-stream heat exchanger design, and the deviation in design size of heat exchanger by using different thermal conductivity models may reach up to 7.5%. The future work on how to improve the property models was discussed.